Changing Local Government Responses to Migration in South Africa - Landau, Loren B. (DIE ERDE – Journal of the Geographical Society of Berlin, 2012)
Constitutionally empowered to be a leading force for development, provincial and municipal authorities have been wary of addressing population movements or seeing them as fundamentally tied to socio-economic development. In many instances, authorities fear that developing pro-active, positive responses to migration would only encourage more of it. Whatever the reason, budgeting and planning exercises make little reference to extended population projections or other insights into the relationships among mobility, livelihoods, and community development. As the population continues to move, the shortcomings of these planning exercises and interventions have become increasingly evident in terms of limited access to critical services, physical and economic insecurity, marginalisation, and social conflict. This essay explains why and suggests means of addressing these challenges.